A review of the critical factors affecting Islamic market mechanisms in Malaysia - Ali, Md Arphan; Rahman, Muhammad Khalilur; Rahman, Mahfuzur; Albaity, Mohamed; Jalil, Md. Abdul (Emerald Publishing Group, 2015)
Purpose – The purpose of this paper is to explore the critical factors that influence Muslim consumers’ motivation towards the Islamic market mechanism.